The Relationship between Gadgets Usage and Adolescent Social Interaction Patterns in SMP Negeri I Sitoluori District - Septian Sebayang (Institute of Computer Science (IOCS), 2019)
As a technology development, human make a good skill to create mechanic equipment for easier human life. Relationship human with new mechanic equipment and easy to use was not separate, that thing called gadget. This research aim is to know relationship gadget using to tennagers social interaction pattern. This research used analysis methods with sample part of population with total sampling was 35 respondents. This research was collected in di SMP Negeri I Kecamatan Sitoluori. Based on analysis data was resulted value p=0.00, which p< α, so any relationship frequency of gadget using to tennagers social interaction pattern. Based on analysis data was resulted value p=0.00, which p< α, so any relationship facility of gadget using to tennagers social interaction pattern. Recommendation for tennagers to make leisure time much more with face to face around social environmental and add activities in outside school hour. Using gadget in frequently can make bad influence for social relationship and disturb health status.